Egg size, chick development, and the nest departure decision of the Thick-billed Murre. - Hipfner, James Mark. (University of Ottawa (Canada), 1996)
In this thesis, I examine the factors that influence egg size, chick development, and the nest departure decision of young Thick-billed Murres, Uria lomvia. The study was conducted at a colony of 30,000 breeding pairs at Coats Island, N.W.T., Canada, in 1994 and 1995. Experienced birds initiated egg formation earlier in the season, and deposited more yolk per day, than younger birds. Among experienced pairs, egg size and laying date were unrelated; eggs laid by young birds at the same time as those of experienced pairs were similar. There was a positive relationship between egg size and the rate at which nestling Thick-billed Murres grew their wing feathers. Growth rate in mass was independent of egg size. Chicks with long wings left the nest to go to sea at a younger age than those with shorter wings in one of two years. The chicks of high quality, experimentally-delayed breeders grew as quickly, and departed at similar mass, as those of unmanipulated early-breeding birds. I conclude that the poor quality of late-breeding birds, more than a seasonally-deteriorating environment, causes the declines in growth of nestlings. I tested two predictions of the Ydenberg model of alcid nest departure for the Thick-billed Murre, which employs a nest departure strategy intermediate within the Alcidae. Among and within colonies, was little support for the model. I suggest that there are developmental and behavioural considerations in the nest departure decision not adequately explained by the Ydenberg model. I propose that the strategy centres around getting the chick from the cliff to the sea as quickly as possible, but with the mortality risk involved in making the transition minimized. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.